In-vivo confocal microscopy: comparison of Keratocytes cell density (KCD) between Femtosecond LASIK (FS-LASIK) and Photorefractive keratectomy (PRK) at one month follow-up - Mat Rejab @ Md Rejab, Noorshazana; Hilmi, Mohd Radzi; Mohd. Kamal, Khairidzan; Md Mustafa, Md Muziman Syah (2019)
Sixteen eyes of 8 participants who underwent FS-LASIK and PRK involved in this prospective nonrandomised study. Inclusion criteria includes of having moderate to high myopia (spherical equivalent, SE: - 3.25D to 9.25D).A flap was created and repositioned back after ablated in FS-LASIK, while in PRK the entire corneal epithelium was removed(flap-less)before ablated. Central corneas were scanned throughout their full thickness using HRTIII/RCM during baseline and post-operative 1 month by single examiner. Morphologic modifications of KCD were evaluated. Using image analysis, KCD was measured in cell/mm2. Two images with non-artefact were selected from each stromal layer for evaluation of KCD and the average mean was taken for analysis. KCD was manually calculated within a region of interest (ROI)set at 0.16mm2 by modification of brightness and contrast. Cells which are more illuminated and refringent were selected and analysed using Wilcoxon signed-rank and Mann-Whitney U test.